Habitat Preference of the Greater One-Horned Rhinoceros (Rhinoceros unicornis Linn.) in the Baghmara Buffer Zone Community Forest, Chitwan National Park, Nepal - Gurung, Anupa; Chalise, Mukesh Kumar (Nepalese Journal of Zoology, 2015)
The Greater One-Horned Rhinoceros (Rhinoceros unicornis Linn.) is listed in Appendix I of the Convention on International Trade in Endangered Species of wild fauna and flora (CITES). A year round (October 2010 to September 2011) research was conducted in the Baghmara Buffer Zone Community Forest (BBZCF), located in the central lowland of Nepal, covering an area of 215 hectares, to collect information on the habitat types of the study area and the habitat preference of the Greater One-Horned Rhinoceros in that area. A total of four nested quadrates (n=4) that were already laid on transects traversing east to west were randomly selected to collect information about the habitat types and the habitat preference of the Greater One-Horned Rhinoceros in the study area. The four nested quadrates, representing the major habitat types of the study area, were laid in four different sites of the Community Forest, Bandevi area (Forest habitat type), Kholsa forest area (Riverbed Forest habitat type), Macchan area (Grassland habitat type) and Riverside forest area near the Budi Rapti River (Riverside Forest habitat type). On the basis of the observed frequency of the animal locations and the availability of their indirect signs studied in the four habitat types of the study area, it was found that the Greater One-Horned Rhinoceros preferred the Grassland habitat type the most in the winter and the monsoon seasons; and likewise the Forest habitat type in the summer season as their habitats.